НУРАБЫЛЛА ЖЫРАЎ МЕКТЕБИ ГИНЕАЛОГИЯСЫ ХАҚҚЫНДА ГЕЙПАРА ОЙЛАР - Аяпов, С.Б. (SCIENCE and SOCIETY, 2022)
This article tells about the life and creative activity of Nirabulla Qorajon son, his students and descendants, who left a bright mark in the art of karakalpak dzhirovism. In addition, detailed information is given about the unique voice, performance skills and repertoire of giraffes such as Esemurat, Ajimurat, Atamurat, Turganbay.
Keywords: kobiz; fat; fat school; epic; proverb; literary heritage; tradition